Polemic Works of John of Damascus on the Holy Quran and its Impacts on the Medieval Ages; Theologians and Crusade - Nusairah binti Ramli (Universiti Sains Islam Malaysia, 2024)
This research investigates the ideas of John of Damascus on the Quran the impacts of his ideas to the medieval age theologians and the crusade.According to John,the Quran is not a revelation,prophet Muhammad(P.B.U.H) is a false prophet and Islam is not a true religion.The misunderstanding about the Quran,prophet Muhammad (P.B.H) and Islam was recycled by some of the theologian’s scholars from medieval ages and used as doctrinal weapon to unite Christians while attacking the Quran and the Islamic belief.This research is divided into four parts and aimed to demonstrate timeline of scholars involved in this long period until the crusade happened and the effects from the influences of all the scholars and also the translations of their works. By using descriptive analysis,this research describes the Christian Criticisms on the Quran during the early ages of Umayyad Caliphate (661-750) and the Abbasid caliphate (750-1258) and the political and educational life of John and the presentation of his works.Through one of his main work,namely, ‘the Heresy of the Ishmaelite’,the heresies about the Quran,prophet Muhammad (P.B.U.H) and Islam are represented.The similar ideas found in the other Christians apologies which not only discussed the misunderstanding but also propagate the ideas during the crusade. All the examples explain how the misunderstanding of the Quran, prophet Muhammad (P.B.U.H) and Islam has sustained for centuries.Finally, this research applies notion of John theoretically using the historical references of the crusade and the impact of translations from more selected scholars.Thus, the research analysis combines the theory and the practical of the notion by the scholars,especially in the crusade. Consequently, this research can be concluded as follows. Firstly, the misunderstanding of the Quran,prophet Muhammad (P.B.U.H) and Islam comes from the text,doctrine or discipline,written to defend Christianity; secondly,this affects personally to Christians and unaware Muslimms; thirdly,the misunderstanding may also affect educated Christians,laymen,church leaders,who,determine to interpret biblical text freely, with their personal exegesis and ultimately incorrectly.From this interpretation they may deduce and sustain a new doctrine about the Quran,prophet Muhammad (P.B.U.H) and Islam that fills with religious fanaticism and extremism.